PENGAKUAN UTANG - PIUTANG DALAM PERJANJIAN PEMBIAYAAN BERDASARKAN PRINSIP MURABAHAH PADA BANK SYARIAH MANDIRI CILEGON - Faisal Amri (FEB Universitas Sultan Ageng Tirtayasa, 2019)
Debt or loan is a transaction between two parties who hand over their money to another voluntarily to be returned to him by the second party with a similar matter. In the murabahah financing agreement practiced by independent Islamic banks there are two deeds agreed upon and signed between the independent Islamic bank and the customer, namely the financing contract based on the murabahah principle made under the hand and SKMHT made before the Notary / PPAT. The analytical method used is a normative juridical approach which states that the law is identical to written norms made and promulgated by an authorized institution or official. From the results of this study, there are two deeds, namely a deed made under the hands of an independent Islamic bank and a deed made by a Notary / PPAT. In the two deeds written the number of debt or loan obligations that must be returned by the customer to the independent Islamic bank is not the same or there is a difference. So that the difference can be interpreted as excess cash returns from the value of debt.